Revolutionizing English Speaking Skills: Unleashing the Power of OmeTV Application for Student - Haris, Aisyah; Rauf, Wahyuddin; Saputra, Wongso Adi (Jurnal Edukasi Saintifik, 2025)
English speaking skills are an essential aspect in the era of globalization. This research investigates the possibility of using the OmeTV app to enhance English-speaking abilities. Using OmeTV's live video chat, students can communicate directly with native speakers about different subjects. This study utilizes a qualitative method with a solitary case study to thoroughly examine students' experience enhancing their English speaking abilities using the OmeTV app. Information was gathered via semi-structured discussions and non-participatory observations and then examined using content analysis to uncover underlying meanings and trends. The findings of this research are anticipated to offer a more comprehensive insight into the factors that impact effective language acquisition in a digital context.